THE ANALYSIS PREPAREDNESS SEMBIRING GENERAL HOSPITAL DELI TUA, DELI SERDANG REGENCY FOR FACING DISASTER - Afrilius Simanjuntak; Herlina J. El-Matury; Megawati Sinambela; Jon Piter Sinaga; Saiful Batubara (Jurnal Penelitian Kesmasy, 2021)
Indonesia as a country with a high risk of disaster needs to prepare hospital health facilities with an optimal level of preparedness. This study aims to analyze the preparedness of the Sembiring Deli Tua General Hospital in dealing with disasters based on the 2nd edition of the Hospital Safety Index (HSI) instrument issued by WHO in 2015 in Indonesian language which is validated. This study uses a mixed method, which combines quantitative and qualitative methods to answer the research objectives. The key informants in this study were the Deputy Director of the Sembiring Deli Tua Hospital in the field of General Administration and Human Resources, and tough informants from a number of hospital employees who were related to the research topic. The research begins with an assessment of the preparedness of the Sembiring Deli Tua Hospital with the HSI instrument. The results of the assessment are analyzed based on Structural Elements, Non-Structural Elements, and Elements of Emergency and Disaster Management. Further analysis is carried out by verifying the results of the assessment with observational data, in-depth interviews, and reviewing documents to reveal things that are considered important to answer research problems.Based on the analysis of Structural Safety Elements with an HSI score of 1 including level A (ready to face disasters), Non-Safety Structural Elements with a score of 0.952 including level A (ready to face disasters), and Emergency and Disaster Management Elements with an HSI score of 0.763 including the level category A (ready to face disaster). Based on the analysis of these three elements, it was found that the Sembiring Deli Tua General Hospital had a total HSI score of 0.938, including the level A category (ready to face disasters).